Reindeer from Sámi offering sites document the replacement of wild reindeer genetic lineages by domestic ones in Northern Finland starting from 1400 to 1600 AD. (February 2021) - Heino, Matti T.; Salmi, Anna-Kaisa; Äikäs, Tiina; Mannermaa, Kristiina; Kirkinen, Tuija; Sablin, Mikhail; Ruokonen, Minna; Núñez, Milton; Okkonen, Jari; Dalén, Love; Aspi, Jouni
Highlights: Ancient reindeer from Sámi offering and dwelling sites are genetically similar. Replacement of wild reindeer haplotypes starting from 1400–1600 AD. Finland not the birthplace of large-scale reindeer pastoralism in Fennoscandia. The transition to reindeer herding affected ritual practices of the Sámi. Abstract: Reindeer herding emerged among the indigenous Sámi of Northern Fennoscandia between ca. 800 and 1500 CE. While the details of the reindeer domestication process are still actively debated, it has been hypothesized that the transition to reindeer herding affected Sámi ritual practice, especially animal offerings given at various sacred sites. To explore this hypothesis, we analyzed DNA from reindeer bone samples dating to ca. 1200–1700 CE from Sámi offering sites located in present-day Northern Finland as well as from samples originating from ancient dwelling site in Southern Finland and Kola Peninsula, Russia. The results show that haplotypes related to wild Finnish forest reindeer ( Rangifer tarandus fennicus ) began to be replaced by haplotypes common in modern domesticated reindeer in the faunal assemblages from offering sites starting between 1400 and 1600 CE. The results suggest that, although the role of reindeer herding in the economy of the Sámi communities varied greatly, the transition to reindeer herding may have affected ritual practices, testifying to a shared way of reciprocating with the land and animals.